Chinese informal trade and microplastic pollution with phthalates: A socio-environmental analysis of the José María Izazaga Avenue commercial corridor (2020–2024) - Cauich Carrillo, Fredy Enrique (2025)
This article examines microplastic pollution containing phthalates as a material expression of a socio-economic and political structure linking the informal trade of Chinese products to patterns of environmental deregulation in Mexico City. Focusing on the commercial corridor of José María Izazaga Avenue during the period 2020–2024, the study advances a dual hypothesis: that there is a significant empirical presence of contaminant microplastics in low-cost goods sold within this urban circuit, and that such presence is embedded within a historical genealogy of migrant trade and institutional complicity. Using an interdisciplinary approach that draws on political ecology, trade history, and the analysis of environmental inequalities, the research combines laboratory-based microplastic detection in plastic goods with a sociohistorical investigation of Chinese commercial structures in Mexico. The findings suggest that plastic pollution is not a technical anomaly, but rather part of a structural logic that reproduces environmental and health inequities in marginalized urban contexts. The article concludes that any update to Mexico’s regulatory framework must be accompanied by a critical recognition of the historical role played by migrant informal economies in shaping collective risk.